HUBUNGAN ANEMIA DEFISIENSI ZAT GIZI BESI DENGAN HASIL BELAJAR BIOKIMIA MAHASISWA BIOLOGI FMIPA UNIMED TAHUN 2014 - Uswatun Hasanah (Universitas Negeri Medan, 2015)
ABSTRACT The purpose of this study is to determine the relationship of nutritional iron deficiency anemia as measured by haemoglobin (Hb) blood students with biochemistry learning outcomes of students majoring in biology FMIPA Unimed 2014. Data was collected through direct observation of the examination of blood haemoglobin levels and the value of the course biochemistry students obtained through formative tests conducted during the lecture Biochemistry. The population of the study was all students majoring in Biology Force 2013 that took a course of Biochemistry. Sampling was done by purposive sampling 2013 Extension class which followed the course of biochemistry with researchers as lecturers. Hemoglobin Blood level distinguished female and male students with criteria for no anemia, mild anemia, moderate anemia and severe anemia. The value of Biochemistry learning outcomes categorized as very competent (value A), competent (value B), quite competent (value C) and incompetent (the value of E). Relationship anemia iron deficiency nutritional students value of biochemistry learning outcomes expressed using the cross table. The results shows that students who are not anemia both women and men to obtain the value of learning outcomes studied biochemistry with very competent and competent category (grades A and B). Students who experience anemia only obtain the value of the study of biochemistry with quite competent category. Students who experience moderate anemia obtain the value of incompetent learning outcomes on biochemistry incompetent category (grades E or otherwise does not pass). Kata Kunci : Anemia defisiensi zat gizi besi, hasil belajar